Study on the Performance of Organic Planting Ribbon on the Paddy (Oryza sativa L) Growth and Rice Production - Djojowasito, Gunomo; Pudjiono, Ekoyanto; Maides, Gusra (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
The direct seedling method still has many obstacles i.e. 1) sensitive to kinetic energy of raindrop and irrigation, that it randomize the row of plant, 2) susceptible to rat and bird attack, 3) faster weed growth compare to the cultivated plants and 4) direct seedling machine results the random plant row spacing. The objectives of this research were (1) to know the effect of organic planting ribbon made from enceng gondok and stem of banana on the growth and the yield of rice, (2) to test the effect of decayer fiber materials (urea and ZA) on the growth and the yield of rice. This research was used factorial randomized block design with 3 replications. The first factor was the type of decayer fiber materials which consist of urea (U) and ZA (Z) and the second factor was organic planting ribbon composition, consisted of (K1) 0% stem of banana, 100% enceng gondok, (K2) 10% stem of banana, 90% enceng gondok, (K3) 20% stem of banana, 80% enceng gondok. The result of this research showed that the composition of 80% enceng gondok, 20% stem of banana, and 5 gram ZA resulted the best growth of rice (plant height) and yield of rice (number of panicle per hill and number of grain per panicle). ZA was better decayer fibre materials compared to urea based on the growth of rice (plant height and number of tiller per hill) and yield of rice (number of grain per panicle, percentage sheel of rice content (%), wet weight of rice per panicle (g) and dry weight of rice per panicle (g).Keywords: rice, plant organic ribbon, enceng gondok, stem of banana